Beam tail effect of a performance-enhanced EC-ITC RF gun - 胡桐宁 裴元吉 秦斌 陈曲珊 (Chinese physics C, 2013)
The beam tail effect of multi-bunches will influence the electron beam performance in a high intensity thermionic RF gun. Beam dynamic calculations that illustrate the working states of single beam tail and multi-pulse feed-in of a performance-enhanced EC-ITC （external cathode independent tunable cavity） RF gun for an FEL （free electron laser） injector are performed to estimate the extracted bunch properties. By using both Parmela and homemade MATLAB codes, the effects of a single beam tail as well as interactions of multi-pulses are analyzed, where a ring-based electron algorithm is adopted to calculated RF fields and the space-charge field. Furthermore, the procedure of unexpected deviated-energy particles mixed with an effective bunch head is described by the MATLAB code as well. As a result, the performance-enhanced EC-ITC RF gun is proved to have the capability to extract continual stable bunches suitable for a high requirement THz-FEL.